Live Online Education Efficiency Mediators From the Actor Network Theory Perspective - Czahajda, Radoslaw; Čairović, Neda; Černko, Mitja (Frontiers in Education, 2022)
Purpose The purpose of this research was to explore the conceptual network of live online education efficiency from the Actor Network Theory perspective to reveal different aspects influencing the quality of online training less accounted for in previous research. Methodology Actor Network Theory was used to analyse the qualitative feedback from 100 live online education sessions. Responses from 90 educators and 556 participants were coded into enablers and inhibitors of education quality and further clustered into different actors that might mediate learning success. Findings The key finding of this research is a visual representation of the complex network of actors potentially affecting live online education quality, revealing the interplay of non-human aspects (e.g., hardware, software, session design, and descriptions), as well as human elements (participants and their expectations, educators and their emotional reactions attributed to different actors of the network, organisers, and external mentors/experts). Limitations The piloting qualitative research was conducted within the framework of one educational event, where participants opted in voluntarily to attend and participate in the study. It is a specific educational context different from workplace training and other non-formal education. Practical Implications Learning and development practitioners can find 10 recommendations designed to support the instructional design and delivery of their (online) sessions based on the collective experiences of the study participants and authors. Originality/value It is the first research in the field of live online education, acknowledging and mapping the role of multiple actors posited to play an influential role in the overall quality. It also calls for a transition from “content-focused and controlling” to “contextually-aware and responsive” educator in future research.